Optimization of a Low Volume Extraction Method to Determine Polycyclic Aromatic Hydrocarbons in Aerosol Samples - Scaramboni, Caroline; Neris, Jordan Brizi; do Nascimento, Rita de Kássia Silva; Chiaranda da Rosa, Natasha Leandra; Carvalho, Jonatas Schadeck; Grosseli, Guilherme Martins; Campos, Maria Lucia Arruda Moura; Fadini, Pedro Sérgio; Urban, Roberta Cerasi (Frontiers in Environmental Science, 2021)
This work describes the optimization of an extraction method for the determination of polycyclic aromatic hydrocarbons (PAHs) and their nitro- and oxy-PAH derivatives in atmospheric particulate matter (PM) samples, and demonstrates that this method is also effective for the determination of levoglucosan. The optimization of the extraction solvents was performed using a three-component mixture design with the solvents dichloromethane, methanol, and acetonitrile. The number of extractions, volume of solvent, and duration of extraction in an ultrasonic bath were optimized using a full factorial design followed by a central composite design. The analyses were performed by gas chromatography coupled with mass spectrometry. The optimized conditions of the method were three extractions using 4.0 mL of acetonitrile, with ultrasonication for 34 min. The proposed method presented good linearity (r >0.990) and acceptable precision for low (100 ng mL-1, RSD: 1-16%), medium (300 ng mL-1, RSD: 1-19%), and high (500 ng mL-1, RSD: 2-16%) concentrations of PAHs. The limits of quantification for different PAHs ranged from 10 to 50 ng mL-1, which were suitable for atmospheric PM. Assessment of the method using sample matrix spiking/recovery assays, as well as use of a reference method, showed good recoveries for levoglucosan and for most of the PAHs and their derivatives, except for the most volatile compounds, which were lost during the evaporation of the solvent. The results for PM samples extracted by the optimized method and the reference method were in good agreement. The proposed method required 97% less solvent than the reference method, shortened the analysis time by 85%, and proved to be accurate and precise for the determination of at least 27 PAHs and their derivatives present in PM samples collected with a low-volume sampler.